Exploring injury severity of Non-Motor vehicle riders involving in traffic accidents using the generalized ordered logit model - Long Zhao; Changshuai Wang; Hongtai Yang; Xiangguo Wu; Tong Zhu; Jianjun Wang (Ain Shams Engineering Journal, 2023)
This study aims to explore potential factors that affect non-motor vehicles (NMV) riders’ injury severity in accidents with motor vehicles (MV). Factors including human characteristics, vehicles, road features and environmental conditions were investigated. Police-reported crash data from the period of 2007 to 2017 in Xi’an, China were used to develop the generalized ordered logit models. Model results revealed that NMV riders’ injury severity was significantly influenced by rider’s Hukou, type of NMV, type of roadside protection, road structure, linearity, weather, accident time, light condition and visibility level. Besides, factors involving NMV rider’s age, compulsory third party insurance, type of MV, season, road type will increase their risk of suffering from serious/fatal injuries. Research findings are beneficial in helping policymakers to develop measures to improve NMV riders’ safety in China, such as isolating NMV and MV, educating drivers especially those from rural areas, and improving road and environment conditions.